Determining the behaviour of clay under repeated loading condition using the CRS oedometer - Tuncan, Ahmet Mustafa. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
Over the past several years, considerable advance have been made in understanding and reasonably predicting the behaviour of soil during repeated loading with different types of apparatus. In this investigation, the consolidation characteristics of remoulded soft clay are studied under repeated loading conditions with the application of low constant rate of strain. Tests are carried out with CRS consolidation apparatus. In this research the variables chosen and their levels were as follows ; sustained load with (....) , load intensity (dynamic load) in percent with (...) and number of cycles with (...). The tests results with respect to chosen variables show that the dynamic void ratio decrease of a soil reach its maximum value under 1 kg/cm of sustained load. The kult and kmax·values are mostly effected due to the increase of the sustained load.
Keywords: Soil consolidation.; Clay soils.; Clay minerals.; Strains and stresses -- Measurement.